In vitro multiplication of yellow dragon fruit (Hylocereus megalanthus) from seedlings obtained in vitro - Mállap-Detquizán, Gerardo (2021)
Introduction. The nutritional properties, antioxidant capacity, and commercial value of the yellow dragon fruit are attractive for its sowing; therefore, it is necessary to study technological improvements for its propagation. Objective. To evaluate the feasibility of in vitro establishment and multiplication of yellow dragon fruit, with the use as explants of seedlings from the in vitro germination and various hormonal sources. Materials and methods. The experiment was developed in the Plant Physiology and Biotechnology Laboratory of the Universidad Nacional Toribio Rodriguez de Mendoza, Peru, between February and June 2020. Four treatments were evaluated for germination [control: sterile water (3 mL), E1: MS (50 %), sucrose (30 g L-1), agar (6 g L-1), E2: AG3 (250 mg L-1), E3: MS (100 %), sucrose (30 g L-1), agar (6 g L-1), AG3 (250 mg L-1)] and multiplication [control: MS (100 %), sucrose (30 g L-1), agar (7 g L-1), M1: MS (100 %), sucrose (30 g L-1), agar (7 g L-1), coconut water (10 ml L-1), M2: MS (100 %), sucrose (30 g L-1), agar (7 g L-1), coconut water (20 ml L-1), activated carbon (2 g L-1), M3: MS (100 %), sucrose (30 g L-1), agar (7 g L-1), BAP (0.10 mg L-1), ANA (3 mg L-1)]. The evaluated variables were: germination (%), number and length of shoots and roots, callus formation (%), rooting (%), and the number of areoles. Results. The best germination (100 %) was obtained in the E1 medium, with more than three roots and two shoots per seedling (2,64 cm). The M2 medium generated the best multiplication, with 82.5 % rooting, 1.66 cm shoots and 1.86 areoles, and less presence of callus tissue (60 %). Conclusion. The micropropagation of yellow dragon fruit was achieved by using seedlings obtained in vitro as an explant source.